The influence of parathyroid hormone 1-34 on the osteogenic characteristics of adipose- and bone-marrow-derived mesenchymal stem cells from juvenile and ovarectomized rats. Issue 8 (August 2019) - Osagie-Clouard, Liza; Sanghani-Kerai, Anita; Coathup, Melanie; Meeson, Richard; Briggs, Timothy; Blunn, Gordon
Abstract : Objectives: Mesenchymal stem cells (MSCs) are of growing interest in terms of bone regeneration. Most preclinical trials utilize bone-marrow-derived mesenchymal stem cells (bMSCs), although this is not without isolation and expansion difficulties. The aim of this study was: to compare the characteristics of bMSCs and adipose-derived mesenchymal stem cells (AdMSCs) from juvenile, adult, and ovarectomized (OVX) rats; and to assess the effect of human parathyroid hormone (hPTH) 1-34 on their osteogenic potential and migration to stromal cell-derived factor-1 (SDF-1). Methods: Cells were isolated from the adipose and bone marrow of juvenile, adult, and previously OVX Wistar rats, and were characterized with flow cytometry, proliferation assays, osteogenic and adipogenic differentiation, and migration to SDF-1. Experiments were repeated with and without intermittent hPTH 1-34. Results: Juvenile and adult MSCs demonstrated significantly increased osteogenic and adipogenic differentiation and superior migration towards SDF-1 compared with OVX groups; this was the case for AdMSCs and bMSCs equally. Parathyroid hormone (PTH) increased parameters of osteogenic differentiation and migration to SDF-1. This was significant for all cell types, although it had the most significant effect on cells derived from OVX animals. bMSCs from all groups showed increased mineralization and migration to SDF-1 compared with AdMSCs. Conclusion: Juvenile MSCs showed significantly greater migration to SDF-1 and significantly greater osteogenic and adipogenic differentiation compared with cells from osteopenic rats; this was true for bMSCs and AdMSCs. The addition of PTH increased these characteristics, with the most significant effect on cells derived from OVX animals, further illustrating possible clinical application of both PTH and MSCs in bone regenerative therapies. Cite this article :L. Osagie-Clouard, A. Sanghani-Kerai, M. Coathup, R. Meeson, T. Briggs, G. Blunn. The influence of parathyroid hormone 1-34 on the osteogenic characteristics of adipose- and bone-marrow-derived mesenchymal stem cells from juvenile and ovarectomized rats. Bone Joint Res 2019;8:397–404. DOI: 10.1302/2046-3758.88.BJR-2019-0018.R1.